2017
DOI: 10.1142/s1793292017501429
|View full text |Cite
|
Sign up to set email alerts
|

A Clean Hydroprocessing of Jatropha Oil into Biofuels over a High Performance Ni-HPW/CNT Catalyst

Abstract: The nickel (Ni) and phosphotungstic acid (HPW) supported on carbon nanotubes (CNT) were prepared by impregnation method for hydroprocessing of Jatropha oil. The Ni-HPW/CNT catalyst was characterized by XRD, XPS, FT-IR, N2 adsorption-desorption, SEM, NH3-TPD, and TGA. The effects of reaction parameters, such as reaction temperature (280–400[Formula: see text]C), time-on-stream (0–100[Formula: see text]h), types of support, the amount of added HPW, and coking deposition were investigated. The cracking performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…The introduction of another metal catalyst enhanced the homogeneity morphology and formation of small metal particles on the surface of MWCNTs, but at the expense of metal particles embedded inside the support as the actual amount of metal, particle traces were lower than the theoretical amount [137]. Similar results were observed for the EDAX mapping of Ni-HPW/MWCNT at various loading of HPW, as the experimental value of chemical element contents was lower than the theoretical values although they were homogeneously dispersed on MWCNT [138]. However, the metal loading of a particular metal type influences the degree of deoxygenation.…”
Section: Multi-walled Carbon Nanotubesupporting
confidence: 73%
See 2 more Smart Citations
“…The introduction of another metal catalyst enhanced the homogeneity morphology and formation of small metal particles on the surface of MWCNTs, but at the expense of metal particles embedded inside the support as the actual amount of metal, particle traces were lower than the theoretical amount [137]. Similar results were observed for the EDAX mapping of Ni-HPW/MWCNT at various loading of HPW, as the experimental value of chemical element contents was lower than the theoretical values although they were homogeneously dispersed on MWCNT [138]. However, the metal loading of a particular metal type influences the degree of deoxygenation.…”
Section: Multi-walled Carbon Nanotubesupporting
confidence: 73%
“…The study of Asikin-Mijan et al has concluded that the high dosages of Fe and Zn (in NiO-Fe 2 O 3 and NiO-ZnO catalysts) contribute to inefficient deoxygenation, as the enhancement of n-(C 15 +C 17 ) selectivity was observed in low metal loading with a large density of weak and medium acidic sites along with strong basic sites [139]. As from the study by Yang et al, the higher loading of HPW (i.e., 50 wt% and 60 wt%) led to lower total pore volume, specific surface area, and pore diameter as compared to low loading of HPW as the pores of support were clogged by excessive catalyst content [138].…”
Section: Multi-walled Carbon Nanotubementioning
confidence: 89%
See 1 more Smart Citation